HUBUNGAN SOSIAL PRODUKSI ANTARA PT.ARVENA SEPAKATDENGAN MASYARAKAT DALAM POLA KEMITRAAN PERKEBUNAN KELAPA SAWIT DI DESA AUR CINA KECAMATAN BATANG CENAKU - Sahbela "; Syamsul Bahri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Partnership relations as a one form of cooperative relationship between the local communities with the oil palm plantations the company as owner of capital and technology and based on the existence of an agreement between the companies to conduct and the people who will partner, called the partnership agreement plasma core palm oil plantations. The purpose of this study is to know and analyze the social relations of production by PT. ArevenaSepakatwith society and palm development, as well as to know and analyze the social relationships form a partnership with oil palm plantations with local society in the village AurCina. Survey research methods approach. The research was conducted in the village AurCina District of BatangCenaku Indragiri Hulu with research subjects are people who partnered with PT. ArvenaSepakat. Data collection using primary data interviews. Once the data is collected qualitative the data were analyzed in descriptive.Research results show that a social relations of production that do PT.ArvenaSepakat with the society in terms of social plantation is used by the local community as a the realization or form of government respect the success that can improve their quality of life in both the economy and reduce unemployment areas accordance with the expectations of the government and the company. Meanwhile, a form of social relationship with the the pattern of oil palm plantations partnership with the local communities Aur Rural China in terms of economy where oil palm can affect people's income, it inidisebabkan by a nice garden and produce good fruit in the garden anyway. If the crops that have been harvested successfully realized in the form of money (of rupiah) then it could affect the economies of local communities.Keyword :Relationship Social Of Economic, The Pattern Of Partnership, Oil Palm Plantations